1992
DOI: 10.1080/07328319208017817
|View full text |Cite
|
Sign up to set email alerts
|

A New Method of Synthesis of Fluorescently Labelled Oligonucleotides and Their Application in DNA Sequencing

Abstract: A new approach to the chemical synthesis of oligonucleotides bearing reporter functional groups based on the modification of cytosine residues during the final deprotection step is reported. The application of the fluorescently labelled primer for the automated DNA sequencing is shown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…Then we used DMAP as an additive, instead of HOBT, to improve coupling performance. A catalytic amount of DMAP is commonly used with carbodiimide coupling reagents (22)(23)(24)(25)(26)(27), and recently, we found that DMAP greatly increases the speed and efficiency of amide formation with uronium or phosphonium coupling reagents (2). However, there have only been a few other reports of DMAP used with uronium (47-50) or phos-phonium (46,51) coupling reagents.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Then we used DMAP as an additive, instead of HOBT, to improve coupling performance. A catalytic amount of DMAP is commonly used with carbodiimide coupling reagents (22)(23)(24)(25)(26)(27), and recently, we found that DMAP greatly increases the speed and efficiency of amide formation with uronium or phosphonium coupling reagents (2). However, there have only been a few other reports of DMAP used with uronium (47-50) or phos-phonium (46,51) coupling reagents.…”
Section: Resultsmentioning
confidence: 99%
“…This problem becomes even more pronounced when coupling must be made through a secondary alcohol (22,23) such as the 3′-OH group in nucleosides. Therefore, we wanted to find coupling conditions which would form the required ester linkages faster and more efficiently than the carbodiimide coupling reagents previously used (22)(23)(24)(25)(26)(27).…”
Section: Introductionmentioning
confidence: 99%
“…nucleic acids and synthetic oligonucleotides, are extremely useful in many areas of molecular biology. The automated DNA sequencing method utilizes rhodamine derivatives (11)(12)(13) and fluorescein derivatives (14)(15)(16)(17)(18)(19). Other non-radioactive systems [fluorochromes (20)(21)(22)(23), enzymes (24)(25)(26)(27), biotin based (28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38) or hapten (39)(40)(41)(42), digoxigenin (43 -44)] are used to label oligonucleotide probes for diagnostic applications.…”
Section: Introductionmentioning
confidence: 99%
“…Initially limited to the commercially available uridine derivative, the procedure was subsequently extended to fluorescein-ATP and -CTP (Igloi, 1996a)(essential for retaining the complementarity of the 3' terminal nucleotide) and remains to date the only direct enzymatic, template independent method for labelling preexisting primers. Despite the proven advantages of this enzymatic procedure in terms of speed and economy during a genome project , Markiewicz et al (1997), apparently unaware of previous publications, described the chemical synthesis of 3' end labelled primers and their application in DNA sequencing.…”
Section: Reaction According To Sangermentioning
confidence: 99%